ASSESSMENT OF GROUNDWATER HEAVY METAL CONTAMINATION IN HADEJIA METROPOLIS, JIGAWA STATE, NIGERIA - AHMED, GARBA; Yahaya, Muhammad; Muhd, Amina Ibrahim (FUDMA Journal of Sciences, 2023)
Heavy metal content in groundwater sources is of growing concern, as they are known to be persistent in nature and have been found to bio-accumulate in animals and plants. They have been found to cause detrimental health effects to human beings; therefore these necessitate the need to assess level of heavy metals in water sources. This study was carried out to evaluation the quality of groundwater samples from twenty five selected boreholes in Hadejia and Atafi Districts of Hadejia Local Government Area, Jigawa State, Nigeria. Selected heavy metals:- Cadmium, Chromium, Iron, Manganese and Lead were determined using atomic absorption spectrophotometry. The results showed that concentrations of Cr(0243 – 0.358mg/L), and Fe(0.967 – 1.359mg/L) were found to be above the maximum permissible limit of Nigerian Standard for Drinking Water Quality and World Health Organization, while, Cd, Mn, and Pb concentrations are below or within the permissible limit in majority of the boreholes. The values for physicochemical variables pH, and TDS were found to be below or within the permissible limit set by the World Health Organization and Nigerian standard for Drinking Water Quality. There is a growing concern about the dangerous health implication of hexavalent chromium consumption in drinking water. It can cause skin and eye irritation, asthma, nasal ulcers, convulsions, acute gastroenteritis, and damage to the liver and kidneys. High iron in water content leads to an overload which can cause diabetes, hemochromatosis, stomach problem, and nausea, it can also damage the liver, pancreas, and heart.
Keywords: Heavy Metals; Groundwater; Contamination